Innovation Processes in Emerging Markets: Empirical Evidence from the Indian Insurance Industry - Anand, Mohit; Monin, Philippe (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2013)
How do organizations innovate to respond to emerging market issues? Building on a multiple-case research design, we study four cases of innovation in the Indian insurance industry. In the first stage of our analysis, we identify seven innovation processes: Demystification, technologization, bundlization, indigenization, retailization, commoditization and segmentation. In the second stage, we find that these seven processes serve as generic responses to three typical issues: management of meanings and values, accessibility and affordability that firms face in emerging markets. Our findings contribute to a better understanding of innovation processes in emerging markets.